THREE-DIMENSIONAL SEISMIC ATTENUATION TOMOGRAPHY IMAGING OF MOUNT GUNTUR USING SPECTRAL FITTING METHOD AND SUMMARY RAYS - HAIKAL SEDAYO (NIM 12403023), MUHAMMAD
This attenuation tomography study was conducted to image the internal structure of mount Guntur using arrival time data and amplitude of P and S waves. The research area is 20 x 20 x 20 km3 and the size of each block used in the model parameterization is 2 x 2 x 2 km3 that includes Guntur's caldera and some other craters in the Mount Guntur complex. The hipocenter position was determined using three-circle method and then relocated by using Grid Search method. We filtered earthquakes data based on area distribution and good waveform. Based on the area distribution of the hipocenters, using blocks of 1 x 1 x 1 km3, and only one hypocenter in one block will be selected (summary ray) based on the best waveform quality. Pseudo bending method was used to conduct ray tracing. Velocity and attenuation inversions were processed by applying a Least Square method (LSQR). Delay time (the difference of P or S wave observed and calculated travel times) was used as input on the velocity inversion. For attenuation inversion, tp* dan ts* were obtained from spectral fitting method. We fitted S and P wave spectra using the spectral fitting equation to determined Ω0, corner frequency (fc) and t*. High attenuation anomaly zone resulting from the attenuation tomogram can be interpreted as an area with high temperature, which may represent the magma under Mount Guntur.